Dampak Knowledge Manajemen Terhadap Kinerja Karyawan Pada Perusahaan Daerah Air Minum Kota Palu - Rossanty, Niluh Putu Evvy; Armawaty, Armawaty; Anas, Muhammad (Fakultas Ekonomi, Universitas Ichsan Gorontalo, 2025)
This study aims to determine the amount of Knowledge management which includes Tacit knowledge (X1) and Explisit knowledge (X2) simultaneously and partially affect employee performance (Y) at the drinking water regional company (PDAM) Palu City. The sample used the Taro Yamane formula so that the sample size was 56 people. Basic data collection through a list of questions that are tested through two stages, namely validity test and reliability test for each question item contained in the questionnaire. The analysis method used is path analysis. Knowledge management which includes Tacit knowledge (X1) and Explisit knowledge (X2) simultaneously has a significant effect on employee performance (Y), the effect is very high and if knoledge management is implemented properly it will improve employee performance. Knowledge management which includes Tacit knowledge (X1) partially has a significant effect on employee performance (Y), although the effect is positive and significant, tacit knowledge is not a dominant determinant of improving employee performance. Knowledge management which includes Explisit knowledge (X2) partially has a significant effect on employee performance (Y), explicit knowledge is the dominant determinant of improving employee performance.